Could Metformin Manage Gestational Diabetes Mellitus instead of Insulin? - Saleh, Hend S.; Abdelsalam, Walid A.; Mowafy, Hala E.; Abd ElHameid, Azza A. (International Journal of Reproductive Medicine, 2016)
Gestational diabetes mellitus (GDM) complicates a significant number of pregnancies. Blood glucose control improves perinatal outcomes. Medical nutrition therapy is the foundation in management. Aim of This Study. To evaluate efficacy of metformin in comparison to insulin for managing GDM. Methods. In prospective randomized comparative study, 150 antenatal women whose pregnancies had been complicated by GDM and did not respond to diet alone were recruited from antenatal clinics at Obstetrics Department in Zagazig University Hospitals from November 2012 to December 2014. They were divided randomly into two groups, 75 patients in each, and were subjected to either insulin or metformin medication. Outcomes were comparing the effects of both medications on maternal glycemic control, antenatal complications, and neonatal outcome. Results. No significant difference in controlling high blood sugar in GDM with the use of metformin or insulin (P=0.95, 0.15). Maternal complications in both groups had no significant difference and fetal outcomes were as well similar except the fact that the hypoglycemia occurred more in insulin group with P value 0.01. Conclusion. Glycaemic control in GDM can be achieved by using metformin orally without increasing risk of maternal hypoglycemia with satisfying neonatal outcome.